2004
DOI: 10.1097/01.rli.0000112089.66448.bd
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pulse and Respiration on Spinal Cerebrospinal Fluid Pulsation

Abstract: The pulsation in the lower spine seems to be related to a second motor of CSF movement because there is a rising respiratory influence and a reappearance of pulsation waves. Physiological spinal CSF pulsation contains a relevant respiratory component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 24 publications
0
58
0
Order By: Relevance
“…The latter communicate freely with the large subarachnoid spaces of the spinal canal via the foramen magnum at the craniocervical junction. Recently, we identified forced inspiration as a major regulator of human CSF flow by applying a novel real-time MRI technique (Dreha-Kulaczewski et al, 2015). In contrast to earlier work using phase-contrast flow MRI techniques with cardiac gating (Greitz et al, 1993;Stadlbauer et al, 2010), the CSF flow related to heartbeat was found to represent only a minor component of the total flow.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The latter communicate freely with the large subarachnoid spaces of the spinal canal via the foramen magnum at the craniocervical junction. Recently, we identified forced inspiration as a major regulator of human CSF flow by applying a novel real-time MRI technique (Dreha-Kulaczewski et al, 2015). In contrast to earlier work using phase-contrast flow MRI techniques with cardiac gating (Greitz et al, 1993;Stadlbauer et al, 2010), the CSF flow related to heartbeat was found to represent only a minor component of the total flow.…”
Section: Introductionmentioning
confidence: 80%
“…In contrast to earlier work using phase-contrast flow MRI techniques with cardiac gating (Greitz et al, 1993;Stadlbauer et al, 2010), the CSF flow related to heartbeat was found to represent only a minor component of the total flow. The unique possibility of measuring CSF dynamics directly by real-time MRI at high spatial and temporal resolution allowed for its evaluation independent of the assumption of any periodicity and thus disclosed inspiration as the dominating driving force (Dreha-Kulaczewski et al, 2015). However, the previously applied real-time MRI method only enabled qualitative identification of flow perpendicular through the imaging section, which precluded more relevant quantitative evaluations of respiratory-driven CSF flux.…”
Section: Introductionmentioning
confidence: 99%
“…heartbeat,~1 Hz), respiration (~0.3 Hz), low frequency (LF) (Mayer wave) (~0.1 Hz) and very low frequency (VLF) oscillations (b0.1 Hz) of different physiological origin (Cheng et al, 2012;Julien, 2006;Obrig et al, 2000a;Phillip et al, 2012;Reinhard et al, 2006;Tong et al, 2011;Toronov et al, 2000;Trajkovic et al, 2011). Also oscillations in the CSF (Droste and Krauss, 1997;Feinberg and Mark, 1987;Friese et al, 2004;Gupta et al, 2010;Kao et al, 2008;Strik et al, 2002) and even periodic displacements of the brain itself (Enzmann and Pelc, 1992;Feinberg and Mark, 1987;Poncelet et al, 1992;Soellinger et al, 2007Soellinger et al, , 2009) may contribute to the non-evoked signals. Spontaneous hemodynamic oscillations are present in the cerebral and extracerebral compartment (Habermehl et al, 2012b).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…It is clear that fMRI signals measured in the cerebrospinal fluid (CSF) compartments do not arise from neuronal activity (i.e., they are not BOLD-related). The ventricular system in the human brain and the fMRI signals reflecting liquor flows are quite complex (Baledent et al, 2001(Baledent et al, , 2006Friese et al, 2004;Kim et al, 2007;Linninger et al, 2009;Stoquart-ElSankari et al, 2007;Sweetman and Linninger, 2011;Windischberger et al, 2002). Some representatives of CSF signals can be extracted directly from data (as voxel time series or as principal components from some CSF areas-e.g., the lateral ventricles) and used as regressors in the general linear model (GLM) during fMRI data analysis.…”
Section: Introductionmentioning
confidence: 99%